Investigation of the properties of reactive MgO-based cements and their effect on performance - Mi, Tangwei (2024)
Reactive MgO cement (RMC) is a promising alternative cementitious material benefiting from a relatively low calcination temperature during its production and strength development in concrete formulations linked with its CO2 sequestering capacity. One of the main challenges with RMC is the variations in its performance in line with the significant differences observed in the properties of the main phase, MgO. To identify and analyze the effects of these properties on the performance of RMC, this study presents a detailed characterization of 9 commercial RMC powders from different sources and precursors and an investigation of their performance in terms of reaction mechanisms and strength development. The results showed that the progress of hydration was highly dependent on the reactivity of RMC, whilst the early stages of the reaction were influenced by the purity. Additionally, agglomeration ratio revealed a strong correlation with the strength after 7 days of carbonation curing and 28 days of hydration. Finally, a regression analysis was employed to propose a model for the prediction of strength based on the initial properties of the RMC powder. The results emerging from this study can serve as a guideline for the selection of most suitable RMC-based binders for various building applications.